Tracking students’ autonomization through emotion traces in logbooks - Chateau, Anne; Candas, Peggy (Studies in Second Language Learning and Teaching, 2015)
Until relatively recently the impact of emotions on language learning has often been ignored and “the nature and contribution of positive emotions and beneficial emotional states deserves further attention” (Bown & White, 2010, p. 433). Our study focuses on a flexible language learning system that combines different elements: work in a virtual learning environment, group work, counselling sessions and a logbook. One of its objectives is to help students progress towards autonomy—defined as “the capacity to take control over one’s own learning” (Benson, 2011, p. 2)—in their learning of English. The logbook has been shown to be useful in helping students become conscious of the new role they have to play in such a system (Chateau & Zumbihl, 2012). A discourse analysis of 100 logbooks from the 2012-2013 cohort of students showed that the traces of emotions they contained could enable us to identify important steps in the development of autonomy, as well as make hypotheses on the links between emotions, students’ self-efficacy and the development of learner autonomy.